HACCP in action food safety case studies - Leigh, Richard; Lavitt, Zane; Video Educational Australia (Australia : Video Educational Australia, 2005)
This program analyses and explains the HACCP scientific system, which identifies specific hazards and measures for their control, ensuring food safety
Title from title screen
Executive producer, Mark McAuliffe ; camera, Peter Zakharov, Zane Lovitt, Richard Leigh ; sound, Wayne Martin, alexy Gudimenko ; graphic, Luhsun Tan
Voice over: Chris Adamidis
Keywords: Food adulteration and inspection; Food handling -- Safety measures